Geographical variation in the density of the white stork Ciconia ciconia in Spain: Influence of habitat structure and climate - Carrascal, L. M.; Bautista, L. M.; Lázaro, E. (Biological Conservation, 1993)
The spatial variation in the density of white storks Ciconia ciconia in Spain is analysed with respect to landscape and meteorological variables. The density of breeding pairs in 1985 was negatively correlated with surface cover of woodlands and shrublands, and posi- tively correlated with the area of dry or wet grasslands, reflecting .food availability and foraging preferences of the storks. Average minimum temperature in April-May (the first .few days after hatching) was also negatively correlated with stork density, and the reproductive success in a colony at El Tietar (Avila) was inversely correlated with the number of days with precipitation in May. The negative influence of minimum temperature and precipitation on breeding density appears to be linked with the mortality of recently born nestlings. Practical recommendations are made for the conserva- tion of the Spanish population of white storks through incentive use of pastures, meadows and 'dehesas' for cattle grazing. Reintroduction efforts must be direct towards zones having large areas of these habitats, and mild weather
Keywords: climate; distribution; habitat; Spain; white stork